Developing a profile of workplace written communication - Attan, Anie (2013)
This paper reports on our study to determine the expectations of employers in respect of graduating students’ written communication. Our study is guided by two research questions: (i) what criteria do employers adopt in evaluating written assignments and (ii) what is the minimum level expected for acceptance of completed tasks in the workplace? Interviews were conducted and samples of graduating students’ written works were shown to informants (human resource personnel) from various fields, among others, the automotive, oil & gas, media, medical and higher education, to elicit their responses to performances of these students. The students had earlier on been given a task to analyse information presented in non-linear texts and to write their analyses in not more than 250 words. The informants were expected to give their responses on whether the quality of written analyses is acceptable or not, their criteria adopted in determining the acceptability of the written analyses, their views of good and poor writing and their expected minimum level of written work quality. Additional preliminary information had also been gathered on type, length, evaluation of the quality of written output and criteria used to assess the quality of written output through a questionnaire survey as a basis for the design of the set task. Results revealed that employers place importance on accuracy of reporting, conciseness, correct use of expressions and terminologies and maturity of thought, among others. From these informed responses, a draft rating scale of the expected writing ability of graduating students deemed relevant for the workplace was developed. Further refinement of the rating scale would follow with validation from the potential employers.